Palliative care out patient consultation service in a teaching hospital in Bangladesh - Ahmad, NU; Haque, MF; Khan, F; Kamal, MM (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jan;20(1):98-103 The abstract of this article is available on the PubMed website